Plocamium cartilagineum field chemotyping - Baker, Bill (IEDA: US Antarctic Program Data Center, 2019)
Abstract: Samples of the red alga Plocamium cartilagineum were collected from the area around Palmer Station, Antarctica, and characterized by gas chromatography for their secondary metabolite content. Patterns in secondary metabolite content were used to establish chemical phenotypes (chemotypes).